Citizens or lobbies: who controls policy? - Paolo Roberti (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2016)
This paper analyses a model of electoral competition with lobbying, where candidates hold private information about their willingness to pander to lobbies, if elected. I show that this uncertainty induces risk-averse voters to choose candidates who implement policies biased in favor of the lobby. Increasing the prior probability of non-pandering candidates can increase the effect of lobbying. If, however, the cost of running for office is sufficiently large, there is no effect of lobbying on policy. The model thus demonstrates that uncertainty on the influence of special interests can lead to large effects of lobbying on policy.
Keywords: D72; D74; D78; 330